(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2026)
Small businesses are the main link in the national economy. At the same time, they play an important role not only in the national economy, but also in the social sphere. The article examines the microeconomic foundations of the sustainable development of small businesses.